1978
DOI: 10.1037/0022-0663.70.3.422
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elaborative prompt condition and developmental level on the performance of addition problems by kindergarten children.

Abstract: A THESIS SUBMITTED IN PARTIAL FULFILMENT OF THE REQUIREMENTS FOR THE DEGREE OF " DOCTOR OF EDUCATION in the Department of Educational Psychology We accept this thesis as conforming to the required standar/d" THE" UNIVERSITY OF BRITISH COLUMBIA March, 197 5 In presenting this thesis in partial fulfilment of the requirements for an advanced degree at the University of British Columbia, I agree that the Library shall make it freely available for reference and study. I further agree that permission for extensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…For instance, basic math skills are more evident when problems are accompanied by concrete referents (e.g., Grunau, 1978) or when materials are made more explicit by eliminating vagueness (e.g., Smith & Cotten, 1980). A number of investigations have demonstrated that one method of making text more explicit and concrete, that of providing advance organizers, is especially effective in increasing comprehension of difficult and/or disorganized text (e.g., Beeson, 1981;Mayer, 1978;Royer & Cable, 1976; see also Chapter 4 in this volume).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, basic math skills are more evident when problems are accompanied by concrete referents (e.g., Grunau, 1978) or when materials are made more explicit by eliminating vagueness (e.g., Smith & Cotten, 1980). A number of investigations have demonstrated that one method of making text more explicit and concrete, that of providing advance organizers, is especially effective in increasing comprehension of difficult and/or disorganized text (e.g., Beeson, 1981;Mayer, 1978;Royer & Cable, 1976; see also Chapter 4 in this volume).…”
Section: Discussionmentioning
confidence: 99%
“…Most mnemonics research in Western cultures has focused'on visual-imagery mnemonics (Higbee, 1979) and would be relevant to Yadai to the extent that Nakane's verbal mediators were high in imagery value. Visual imagery has been found to help the performance of kindergarten children in the United States on difficult addition problems (Grunau, 1978).…”
Section: Some Questions For Researchmentioning
confidence: 99%